2019
DOI: 10.1136/bcr-2018-229064
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-associated autoimmune haemolytic anaemia

Abstract: Treatment paradigms have recently changed with the introduction of immunotherapy; autoimmune toxicities that can arise are frequently very different from the more familiar chemotherapy toxicities. We present a clinical case of autoimmune haemolytic anaemia (AIHA) secondary to pembrolizumab occurring in a 73-year-old male patient being treated for lung adenocarcinoma, who had received 13 cycles of pembrolizumab. Treatment was immediately stopped and he was treated with high dose steroids to which he responded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…We found 377 studies in the database search. After we deleted duplicates and we analyzed full texts, we included 14 case series and 66 individual case reports4,12–98 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…We found 377 studies in the database search. After we deleted duplicates and we analyzed full texts, we included 14 case series and 66 individual case reports4,12–98 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…A review by Tanios et al demonstrated that the first report on Pem-induced hematologic toxicity was published in 2014. 7 Subsequently, as the indications for Pem have increased, including malignant melanoma, 15,16 non-small cell lung cancer, 17,18 and chronic lymphocytic leukemia, 19 there have been increased in reports of hemolytic anemia as an irAE. Pem is available for renal cell carcinoma and UC; Funabashi et al reported real-life a clinical practice study that demonstrated that grade 3 or higher anemia occurred in 2.9% of patients with advanced UC refractory to cisplatin, 20 with a short mean follow-up of 7.7 months.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that the first report on Pem‐induced hematologic toxicity was published in 2014. 7 Subsequently, as the indications for Pem have increased, including malignant melanoma, 15 , 16 non‐small cell lung cancer, 17 , 18 and chronic lymphocytic leukemia, 19 there have been increased in reports of hemolytic anemia as an irAE. Pem is available for renal cell carcinoma and UC; Funabashi et al .…”
Section: Discussionmentioning
confidence: 99%